Institutional Reproduction and Change: An Analytical Framework for Brazilian Electricity Generation Choices - Pavanelli, JoÃ£o Marcos Mott; Igari, Alexandre Toshiro (International Journal of Energy Economics and Policy, 2019)
Energy transitions will be shaped, among other aspects, by their Institutional historical trajectory. Institutions reproduce and change over the time, and these processes have been investigated under different and sometimes confronting approaches. We proposed a framework which articulates different institutionalism approaches to understand the dominance of hydroelectricity in the Brazilian matrix. The framework articulates institutional processes to explain its reproduction and change over time. Findings point out that institutional path dependence and isomorphism have precluded the adoption of other technologies in Brazil. Contrarily, momentary external or internal crisis in the field rapidly fostered the emergence of electricity generation transition from almost fully hydroelectric to a hybrid matrix with thermal (fossil and biomass) and wind power. Crises presented an opportunity to strategic action of social skilled agents on institutional change. This analytical framework improves the integration of complementary theoretical approaches for understanding institutional dynamics in order to guide policymakers. Keywords: Energy Transitions; Institutional Analysis; Brazilian Electricity Sector JEL Classifications: B52, P48, Q42 DOI: https://doi.org/10.32479/ijeep.8056